PENGARUH KEBIASAAN MENABUNG TERHADAP HIDUP HEMAT SANTRI ASRAMA AL-MASYITHOH PADA TABUNGAN HARIAN DI BIRO KEUANGAN PUTRI DARUSSALAM BLOKAGUNG BANYUWANGI - Tutut Wijayanti; Eko Budiywono (Universitas KH. Mukhtar Syafaat, 2025)
The purpose of this study is 1) To find out the saving habits (X) on the life-saving santri of Al-Masyithoh Dormitories at the daily savings in the putri Darussalam finance bureau (Y). 2) To find out the life savings (Y) of the life savings of Al-Masyithoh boarding students on daily savings in the Darussalam financial bureau of Blokagung Banyuwangi (Y). This study uses a quantitative method where there are two variables, namely saving habits (independent) variable and frugal living (dependent) variable. Based on the results of the study note that the Ftest results obtained by simple regression analysis showed that the Fcount value of 4.5840 and Ftable at a significance level of 3.35. F test results are known that the Fcount value is greater than Ftable or 4.5840 > 3.35. Then it can be seen that the independent variable saving habits (X) influences the dependent variable namely life saving santri (Y). So the result of this study is that the saving habits has a positive and significant effect on the Alive Savings of Al-Masyithoh boarding students in the daily savings in the putri Darussalam finance bureau, Blokagung Banyuwangi.